The evolution of the Puf superfamily of proteins across the tree of eukaryotes - Najdrová, Vladimíra; Stairs, Courtney W; Vinopalová, Martina; Voleman, Luboš; Doležal, Pavel (BMC biology, 2020)
BACKGROUND: Eukaryotic gene expression is controlled by a number of RNA-binding proteins (RBP), such as the proteins from the Puf (Pumilio and FBF) superfamily (PufSF). These proteins bind to RNA via multiple Puf repeat domains, each of which specifically recognizes a single RNA base. Recently, three diversified PufSF proteins have been described in model organisms, each of which is responsible for the maturation of ribosomal RNA or the translational regulation of mRNAs; however, less is known about the role of these proteins across eukaryotic diversity. RESULTS: Here, we investigated the distribution and function of PufSF RBPs in the tree of eukaryotes. We determined that the following PufSF proteins are universally conserved across eukaryotes and can be broadly classified into three groups: (i) Nop9 orthologues, which participate in the nucleolar processing of immature 18S rRNA; (ii) 'classical' Pufs, which control the translation of mRNA; and (iii) PUM3 orthologues, which are involved in the maturation of 7S rRNA. In nearly all eukaryotes, the rRNA maturation proteins, Nop9 and PUM3, are retained as a single copy, while mRNA effectors ('classical' Pufs) underwent multiple lineage-specific expansions. We propose that the variation in number of 'classical' Pufs relates to the size of the transcriptome and thus the potential mRNA targets. We further distinguished full set of PufSF proteins in divergent metamonad Giardia intestinalis and initiated their cellular and biochemical characterization. CONCLUSIONS: Our data suggest that the last eukaryotic common ancestor (LECA) already contained all three types of PufSF proteins and that 'classical' Pufs then underwent lineage-specific expansions.
Keywords: LECA; RNA, Messenger; fylogeneze; RNA, Ribosomal, 18S; Phylogeny; Eukaryota; Protein Biosynthesis; proteosyntéza; RNA processing; Amino Acid Sequence; sekvenční seřazení; Puf superfamily proteins; RNA-Binding Proteins; sekvence aminokyselin; RNA-binding protein; RNA ribozomální 18S; messenger RNA; proteiny vázající RNA; Sequence Alignment; Giardia intestinalis